4(2p-8)-6p=20-4(p+6)

Simple and best practice solution for 4(2p-8)-6p=20-4(p+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2p-8)-6p=20-4(p+6) equation:


Simplifying
4(2p + -8) + -6p = 20 + -4(p + 6)

Reorder the terms:
4(-8 + 2p) + -6p = 20 + -4(p + 6)
(-8 * 4 + 2p * 4) + -6p = 20 + -4(p + 6)
(-32 + 8p) + -6p = 20 + -4(p + 6)

Combine like terms: 8p + -6p = 2p
-32 + 2p = 20 + -4(p + 6)

Reorder the terms:
-32 + 2p = 20 + -4(6 + p)
-32 + 2p = 20 + (6 * -4 + p * -4)
-32 + 2p = 20 + (-24 + -4p)

Combine like terms: 20 + -24 = -4
-32 + 2p = -4 + -4p

Solving
-32 + 2p = -4 + -4p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '4p' to each side of the equation.
-32 + 2p + 4p = -4 + -4p + 4p

Combine like terms: 2p + 4p = 6p
-32 + 6p = -4 + -4p + 4p

Combine like terms: -4p + 4p = 0
-32 + 6p = -4 + 0
-32 + 6p = -4

Add '32' to each side of the equation.
-32 + 32 + 6p = -4 + 32

Combine like terms: -32 + 32 = 0
0 + 6p = -4 + 32
6p = -4 + 32

Combine like terms: -4 + 32 = 28
6p = 28

Divide each side by '6'.
p = 4.666666667

Simplifying
p = 4.666666667

See similar equations:

| 28-3c+4=2c+6+c | | 2a+4=6a+8 | | ln(4)+ln(20)=0 | | -7x+9=-2x-21 | | 11-x+4=3x+5-8x | | p=lxw | | (a-4)=44 | | 1+3*10= | | 6y=2x+10 | | 50d-4=3 | | 12n^2-24=0 | | 4a+9=2a+6 | | p=5x-(100+3x) | | 14-(3p+1)= | | 50-7d=6 | | ln(x-1)=0.8 | | (5x-2w)(8x-5w)= | | 81-18y+y^2+y^2=53 | | 4z+2=8-4z | | r=(w-9)(w+9) | | 0=2x^2+15x+15 | | 3y+y=y+12 | | 2x-5x-20=-7+4x-8 | | 6.1a+14=81.1 | | f(x)=2x^3-10x+12x | | 3k-7/3=9 | | 6x-36+8=8x-8 | | x^2-6x+7=180 | | 0=2x^3-10x+12x | | 1a+14=81.1 | | 5x-7=-7x+26 | | X^2+10=10x-14 |

Equations solver categories